Effectiveness of intranasal corticosteroids - Grzincich, G.L.; Capra, L.; Cammarata, et al., M.G. (Acta Biomedica Atenei Parmensis, 2004)
Intranasal corticosteroids (IC) are most commonly prescribed to treat allergic rhinitis (perennial and seasonal). There are now many IC available to treat rhinitis, all effective on nasal obstruction, rhinorrhea, sneezing, itching and post-nasal drip. IC are superior to oral antihistamines for the relief of all nasal symptoms; however, antihistamines are first line therapy if allergic conjunctivitis coexists. At present the data do not support the use of IC in the management of otitis media with effusion (OME), nasal polyposis and sinusitis, but when topical IC are administered together with antibiotic therapy they facilitate a more rapid improvement of symptoms.